Three essays in intraday momentum, market efficiency and market liquidity - Khan, Ali Shakil (2020)
This thesis is composed of three essays which aim to provide a better understanding of intraday market momentum, market efficiency and market liquidity in international markets. These aspects are under researched in international stock markets, particularly in the Chinese stock markets. These issues have become significant as the International markets continue to expand in size and some of them such as China differ considerably in terms of ownership structure, have various share classes and are subject to various trading regulations.